From gear to culture: How technology shapes the world of rock climbing - Gusti Ketut Alit Suputra; John Louise M. Marcaida; Aprianoto Aprianoto; Majid Wajdi; Ni Ketut Sekarti; Dessalegn Mekuriaw (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2025)
Rock climbing is a form of mountaineering that involves navigating steep cliffs, making it a physically demanding and extreme sport. Introduced in Indonesia in the 1970s, it has evolved from local expeditions to international competitions, gaining popularity among youth and adventure seekers. The sport requires both physical prowess and mental agility, blending strength, strategy, and safety. This paper explores the fundamental aspects of rock climbing, focusing on climbing techniques, necessary equipment, and the importance of safety. The objectives are to provide a comprehensive understanding of the sport, highlight its physical and mental benefits, and promote it as a fulfilling and educational activity. These benefits include enhanced physical strength, improved coordination, cognitive skill development, and boosted self-confidence. Data collection involved field observations of rock climbing environments and routes to capture the technical challenges and strategies used by climbers. Interviews with experienced climbers provided valuable insights into their experiences, techniques, and psychological approaches to overcoming obstacles. These qualitative methods allowed for a deeper understanding of the sport's physical, emotional, and technical dimensions. The analysis of the data highlights the sport’s rising international recognition, including its presence in the Olympics. It also underscores the cultural significance of rock climbing in Indonesia and the strategic role it plays in physical and mental development. This paper concludes by advocating for the growth of rock climbing as a popular and enriching sport, with the potential to positively influence personal development.